Regional Differences in Early BP Management After Acute Ischemic Stroke in the ENCHANTED International Randomized Controlled Trials - Chen, Chen; Song, Lili; Yang, Jie; Lindley, Richard; Robinson, Thompson; Arima, Hisatomi; Chalmers, John; Anderson, Craig S.; Wang, Xia (Frontiers in Neurology, 2021)
Background and Aims: Epidemiological studies show significant variations in hypertension management within and between countries. The level of regional variation in early blood pressure (BP) management after acute stroke is uncertain. Methods: Data are from the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED), a partial-factorial, international randomized controlled trial of thrombolysis-eligible acute ischemic stroke (AIS) patients with elevated systolic BP (SBP >150 mmHg) assigned to intensive (target SBP 130-140 mmHg) vs. guideline-recommended (SBP <180 mmHg) treatment; BP management was compared among four regions: Western countries (Italy/United Kingdom/Spain/Australia), China (mainland), other Asia (Hong Kong/Taiwan/Singapore/Thailand/Vietnam/India), and South America (Chile/Brazil/Colombia). Results: These analyses included 2,196 AIS [38% women, mean age 67 (12) years] patients. Commonly used intravenous BP-lowering agents were labetalol, nitroglycerin, and topical nitrates in Western countries; urapidil and sodium nitroprusside in China; nicardipine in other Asian countries; and sodium nitroprusside and labetalol in South America. Chinese patients were less likely to receive BP-lowering treatment in the first 24 h and be treated with multiple agents although they had smaller magnitude of SBP reduction and lower SBP variability. Conclusion: Regional variations in early BP management in acute stroke translated into differences in early BP control parameters.